Effect of Noninvasive Ventilation Mask Design on Upper Airway Washout: A Computational Fluid Dynamics Model. - Clark, Alys R.; O'Hagan, Lomani A.; Fogarin, Jessica R.; Gordon, James A.; Miller, James C.D.; Perera, Ashani M.; Mirjalili, S. Ali (Respiratory Care, 2025)
Background: Noninvasive ventilation (NIV) is a primary treatment for patients with acute hypercapnic respiratory failure. Mask choice is fundamental in the success of NIV. Mask design can influence the fit, comfort, and venting of the instrumental dead space. A new mask has been designed to reduce effect of anatomical dead space by washing out the airway of expired gases at end expiration. The aim of this investigation was to use computational fluid mechanics to model upper airway washout with different NIV mask designs. Methods: A 3D-printed head that represents the face and upper airways was used to construct 3D air space maps to be analyzed by computer simulation software when an individual is using each mask design. The 3D-printed head was mounted on a desktop lung simulator, measuring air flow and pressure at the mask and at the tracheal level during noninvasive therapies. Computational fluid dynamics was used to simulate air flow and CO2 distribution within the airway geometry and used to predict the impact of mask design on CO2 distribution within the upper airways. Results: The models predict distributions of CO2 through the upper airway geometry and show that because of the washout of expired gas in the nasal cavity, the novel mask improved CO2 concentrations at end expiration compared with conventional NIV. In simulations where the mouth and nasopharynx were both open, a 44% decrease in CO2 in the nasal cavities and a 28% decrease in CO2 over the entire upper airway geometry was predicted to result from this washout. Conclusions: Mask design can influence CO2 clearance in the upper airway. NIV with airway washout resulted in more CO2 clearance from the airway compared with a conventional NIV mask. Improved CO2 clearance may facilitate improved alveolar ventilation and subsequent gas exchange.